WHAT IS THE SCIENCE OF COMMUNICATION? A POSSIBLE DEFINITION - Arthur SUCIU (Association of Social and Educational Innovation, 2021)
The article's aim is to provide a definition of the science of communication together with the delimitation of the field of research and the identification of a general research method. The starting point is the general phenomenon of communication in the living world, as the research field of communication science is limited, by successive delimitations, to media discourses. The most important aspect that has been highlighted is the political nature of media speeches. Politics de-homogenizes the discursive mass and at the same time provides a clear criterion for classifying discourses. Thus, insofar as communication is media-based, it is also a political communication. The science of communication is defined as the study of the phenomenon of integration and discursive distancing, in other words of the discursive competition and social negotiation. The starting point of the entire process of definition is the work "Autonomous Discourse. Communication Strategies" (2013).